Tele-Robotic Assisted Dental Implant Surgery with Virtual Force Feedback - Amjad Ali Syed; Amir Mahmood Soomro; Arbab Nighat Khizar; Xing-guang Duan; Huang Qiang; Farhan Manzoor (Indonesian Journal of Electrical Engineering and Computer Science, 2014)
The dental implant surgical applications full of risk because of the complex anatomical architecture of craio-maxillofacial area. Therefore, the surgeons move towards computer-aided planning for surgeries and then implementation using robotic assisted tele-operated techniques. This study divided into four main parts. The first part is developed by computer-aided surgical planning by image modalities .The second part is based on Virtual Surgical Environment through virtual force feedback haptic device. The third part is implemented the experimental surgery by integrating the prototype surgical manipulator with the haptic device poses using inverse kinematics method. The fourth part based on monitoring the robotic manipulator pose by using image guided navigation system to calculate the position error of the surgical manipulator. Thus, this tele-robotic system is able to comprehend the sense of complete practice, improve skills and gain experience of the surgeon during the surgery. Finally, the experimental outcomes show in satisfactory boundaries. DOI : http://dx.doi.org/10.11591/telkomnika.v12i1.3124